Enhanced Antioxidant Activity of Capsicum annuum L. and Moringa oleifera L. Extracts after Encapsulation in Microemulsions - Georgia Batra; Olga Gortzi; Stavros I. Lalas; Anna Galidi; Angeliki Alibade; George D. Nanos (ChemEngineering, 2017)
Carotenoids are powerful natural antioxidants that can easily degrade and are almost insoluble in water. Their incorporation into microemulsions (MEs) can solve these problems. In this study, ethanol extracts (prepared using different protocols) of Capsicum annuum L. (green and red), Moringa oleifera L. leaves, and their mixtures [Red Pepper/Μ. oleifera (50/50 w/w) and Green Pepper/M. oleifera (50/50 w/w)], were encapsulated in MEs for the first time. The encapsulation efficiency was determined and the physicochemical characteristics of the prepared MEs were assessed by particle size, turbidity, centrifugation, and thermal stress determination. The antioxidant activity of extracts and their MEs was determined by the DSC and DPPH methods. Prepared MEs did not present phase separation, creaming, sedimentation, presence of aggregates, or other unacceptable macroscopic drawbacks. Turbidity measurements showed that only small differences in optical density appeared. MEs’ particle size dispersion was found to be around the average value and varied between 10 and 95 nm. The highest resistance to oxidation of crude extracts was observed by the M. oleifera leaf extract, followed by that of Red Pepper/Μ. oleifera (50/50 w/w) mixture, Green Pepper/M. oleifera (50/50 w/w) mixture, Red Pepper and, finally, Green Pepper. The results concerning MEs-encapsulated samples followed the same trend.